ANOXIA AS THE CAUSE OF THE MID-EARLY CAMBRIAN (BOTOMIAN) EXTINCTION EVENT - Zhuravlev A.Yu.; Wood R.A. (My University, 1996)
New and revised Early Cambrian biostratigraphic data allow a quantitative analysis of changes in biotic diversity and extinction rate. The mid-Early Cambrian extinction can now be resolved into two distinct events: the well-known early Toyonian Hawke Bay regression event, and a newly observed but more severe disruption during the early Botomian, here named the Sinsk event. During the Sinsk event, the shallow-water benthos of the so-called Tommotian fauna, together with archaeocyaths and some trilobites, underwent a rapid decline. The Sinsk event is characterized by the significant accumulation of nonbioturbated laminated black shales in tropical shallow waters. Lamination is due to the fine alternation of clay- and organic-rich laminae with calcite-rich laminae containing abundant monospecific acritarchs. These shales are enriched by pyrite and elements typical of anoxic conditions and support a benthic biota of dysaerobic character. Our observations suggest that the extinction during the early Botomian was caused by extensive encroachment of anoxic waters onto epicontinental seas, associated with eutrophication and resultant phytoplankton blooms.
Keywords: Cambrian; Paleozoic::Cambrian; Палеозой::Кембрийская